Effects of a non-conservative sequence on the properties of β-glucuronidase from Aspergillus terreus Li-20. - Yanli Liu (Public Library of Science (PLoS), 2012)
We cloned the β-glucuronidase gene (AtGUS) from Aspergillus terreus Li-20 encoding 657 amino acids (aa), which can transform glycyrrhizin into glycyrrhetinic acid monoglucuronide (GAMG) and glycyrrhetinic acid (GA). Based on sequence alignment, the C-terminal non-conservative sequence showed low identity with those of other species; thus, the partial sequence AtGUS(-3t) (1-592 aa) was amplified to determine the effects of the non-conservative sequence on the enzymatic properties. AtGUS and AtGUS(-3t) were expressed in E. coli BL21, producing AtGUS-E and AtGUS(-3t)-E, respectively. At the similar optimum temperature (55°C) and pH (AtGUS-E, 6.6; AtGUS(-3t)-E, 7.0) conditions, the thermal stability of AtGUS(-3t)-E was enhanced at 65°C, and the metal ions Co(2+), Ca(2+) and Ni(2+) showed opposite effects on AtGUS-E and AtGUS(-3t)-E, respectively. Furthermore, Km of AtGUS(-3t)-E (1.95 mM) was just nearly one-seventh that of AtGUS-E (12.9 mM), whereas the catalytic efficiency of AtGUS(-3t)-E was 3.2 fold higher than that of AtGUS-E (7.16 vs. 2.24 mM s(-1)), revealing that the truncation of non-conservative sequence can significantly improve the catalytic efficiency of AtGUS. Conformational analysis illustrated significant difference in the secondary structure between AtGUS-E and AtGUS(-3t)-E by circular dichroism (CD). The results showed that the truncation of the non-conservative sequence could preferably alter and influence the stability and catalytic efficiency of enzyme.